PERSPECTIVES OF SCHOLARS AND MEDICAL PERSONNEL ON RECONSTRUCTIVE PLASTIC SURGERY FOR ACCIDENT VICTIMS - Yoga Saputra, Dwiki; Nur Aeni, Ira; Riva Putri, Jans; Daya Lestari, Prima; Marsellina, Selly; Supriyadi, Tedi; Faozi, Akhmad (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study analyzes the perspectives of ulama and medical personnel on reconstructive plastic surgery for accident victims, focusing on the dimensions of ethics, Islamic law, and medical practice. Through a qualitative case study approach involving in-depth interviews with scholars and medical personnel in Sumedang Regency, this study reveals that reconstructive surgery is permissible in Islam when it aims to restore bodily functions, according to the principles of maslahah (benefit) and emergency (urgent need). Intention (niyyah) is the main determinant of its legal status, where medical treatment for post-accident recovery is considered na effort to maintain health, while aesthetic surgery without medical indications is considered a violation of sharia. The findings show harmonization between sharia principles and medical needs, with scholars emphasizing that restoration of bodily functions is in line with the concept of hifdzun nafs (preservation of the soul) in Islam. From a medical perspective, reconstructive surgery plays a crucial role in holistic recovery-physical, psychological and social-with success rates varying depending on the type of injury. Medical personnel act as mediators between clinical needs and patients’ religious values, especially through empathic communication and informed consent to overcome religious-based resistance. However, societal stigmatization of plastic surgery as na act of “altering God’s creation” remains na obstacle, impacting on victims’ anxiety and trauma